High and steady or low and rising? : Life-cycle earnings patterns in vocational and general education - Cörvers, Frank [Verfasser]; Heijke, Hans [Verfasser]; Kriechel, Ben [Verfasser]; Pfeifer, Harald [Verfasser] (My University, 2011)
"In this paper, we compare experience-earnings profiles of employees with vocational and general education background in Germany, the Netherlands and the United Kingdom, three countries with fundamentally different education systems. Using Mixed-Effects Linear Regression Models we show that earnings of vocationally educated employees are higher in the initial phase of their career. However, those with a general education background catch up over time in the labor market. Life-cycle differences in earnings are more pronounced in Germany than in the United Kingdom and the Netherlands." (Autorenreferat, BIBB-Doku)
Keywords: Berufliche Qualifikation; Bildungsabschluss; Einkommen; Berufseinmündung; Berufserfahrung